Mid-infrared Supercontinuum Generation to ∼4.7 μm in a ZBLAN Fiber Pumped by an Optical Parametric Generator - Maria Michalska; Petr Hlubina; Jacek Swiderski (IEEE Photonics Journal)
We present mid-infrared (mid-IR) supercontinuum (SC) generation from a step-index fluorozirconate fiber pumped at 2.25 μm. When 70 ps pulses with a peak power of 128 kW were launched into a ZBLAN fiber with a zero dispersion wavelength at 1.603 μm, SC was extended to 4695 nm, with spectral flatness below 10 dB, in the 2.00–4.56 μm range. To the best of our knowledge, this is the first time such a broad and flat mid-IR SC spectrum from a ZBLAN fiber pumped with ps pulses has been achieved. The SC evolution as a function of pump wavelength and pump pulse energy was also experimentally demonstrated.